Screening of medicinal plants from Taman Herba Perlis for acetylcholinesterase inhibitory activity / Norhafizoh Abdul Somat ... [et al.] - Abdul Somat, Norhafizoh; Osman, Che Puteh; Ismail, Nor Hadiani; Yusoff, Zaini; Md Yusof, Yuswanie (Faculty of Applied Sciences, 2019)
In a search for new potential AChE inhibitors, 31 selected medicinal plants from Perlis were collected gathered, air dried and successively extracted using hexane, dichloromethane, and alcohol. The dichloromethane and alcoholic extracts were screened for AChE inhibitory activity using Ellman's method. Out of 31 plant species, the methanol extracts of Rhapis excelsa leaves (97.03 ± 3.71 %), Diospyros blancoi leaves (95.80 ± 1.57 %) and Phyllantus elegans root (83.22 ± 3.08 %) showed the highest AChE inhibitory activity at the concentration of 100 µg/mL.